Biogeochemical properties of seawater measured from the icebreaker Shirase during the 54th Japanese Antarctic Research Expedition in the austral summer, 2012–2013 - Takamura, Tomomi R.; IIDA, Takahiro; NISHIOKA, Jun; ODATE, Tsuneo (国立極地研究所, 2014)
Fig. 1, 2 | http://polaris.nipr.ac.jp/~parc/pub/v004/nipr_parc_183_0004_2013.doc Table 1 | http://polaris.nipr.ac.jp/~parc/pub/v001/nipr_parc_183_0001_2013.xls Table 2 | http://polaris.nipr.ac.jp/~parc/pub/v002/nipr_parc_183_0002_2013.xls Table 3 | http://polaris.nipr.ac.jp/~parc/pub/v003/nipr_parc_183_0003_2013.xls departmental bulletin paper